2014
DOI: 10.4137/ehi.s16014
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Larvicide-Resistant Catch Basins from Three Years of Larvicide Trials in a Suburb of Chicago, IL

Abstract: The tens of thousands of catch basins found in many urban areas are a primary target of local vector control agencies for seasonal application of extended-release larvicides. A concern with using larvicides in these structures is that active ingredients can be hampered by high flows, debris, and sediment, all of which are common to these structures. As such a certain proportion of basins may be “resistant” to larvicide treatments due to site specific characteristics that may promote these and other factors tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…MET has the advantage to directly assess the presence of emerging adults (as opposed to larvae or pupae) without the need of high numbers of larval dips inside the catch basins (which are needed to collect a representative number of larvae/pupae [ 47 ]), thus also eliminating the need of rearing larvae to the adult stage, when species with similar larval morphology are present [ 48 ]. Moreover, MET can be exploited to assess the lethal effect of larvicide-treatments in catch basins, which represent a fundamental component in the control of the abundance of urban mosquitoes [ 49 ] and are very commonly carried out in infested municipalities in Italy [ 21 ]. Results obtained showed that, although all monitored catch basins were shown to be visited by Ae.…”
Section: Discussionmentioning
confidence: 99%
“…MET has the advantage to directly assess the presence of emerging adults (as opposed to larvae or pupae) without the need of high numbers of larval dips inside the catch basins (which are needed to collect a representative number of larvae/pupae [ 47 ]), thus also eliminating the need of rearing larvae to the adult stage, when species with similar larval morphology are present [ 48 ]. Moreover, MET can be exploited to assess the lethal effect of larvicide-treatments in catch basins, which represent a fundamental component in the control of the abundance of urban mosquitoes [ 49 ] and are very commonly carried out in infested municipalities in Italy [ 21 ]. Results obtained showed that, although all monitored catch basins were shown to be visited by Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Insecticide-based larvicides (e.g. those that directly lead to larval mortality, such as Bacillus thuringiensis , bti) that present low efficacy on larval mortality in a catch basin [ 9 , 11 , 48 ] could be relieving the population from strong competitive pressure, leading to an initial reduction in productivity but a rapid bounce-back of populations after rain events flush or dilute chemicals in catch basins. Conversely, insect growth regulators (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Such a relationship is supported through our investigation of Model A* sensitivity to adult and larval perturbation. The interaction between competition release and insecticide regime efficacy, though little studied, can have high value in informing vector control strategies relying on larval control [ 1 , 9 , 11 , 48 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations